1985
DOI: 10.1128/jb.164.2.918-921.1985
|View full text |Cite
|
Sign up to set email alerts
|

Positive selection procedure for entrapment of insertion sequence elements in gram-negative bacteria

Abstract: We constructed the broad-host-range plasmid pUCD800 containing the sacB gene of BaciUus subtilis for use in the positive selection and isolation of insertion sequence (IS)Y'elements in gram-negative bacteria. Cells containing pUCD80 do not grow on medium containing 5% sucrose tinless the sacB gene is inactivated. By using pUCD800, we isolated a 1.4-kilobase putative IS element from Agrobacterium tumefaciens NTlRE by selection for growth on sucrose medium. This putative IS element'appears to be unique to Agroba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
141
0
3

Year Published

1992
1992
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 448 publications
(144 citation statements)
references
References 22 publications
0
141
0
3
Order By: Relevance
“…Puri-fied transconjugants were grown i n low-salt-Bertani medium overnight and 105-10q cells were spread on low-salt Luria-Bertani medium plates containing IS % sucrose. The presence of an intact sacB gene encoding the periplasmic enzyme levansucrase kills gram-negative bacteria due to the production of levan in the periplasm (Gay et al, 1985). Thus, positive selection for sucrose resistance allows the collection of mutants with an allelic exchange.…”
Section: Strains and Plasmidsmentioning
confidence: 99%
“…Puri-fied transconjugants were grown i n low-salt-Bertani medium overnight and 105-10q cells were spread on low-salt Luria-Bertani medium plates containing IS % sucrose. The presence of an intact sacB gene encoding the periplasmic enzyme levansucrase kills gram-negative bacteria due to the production of levan in the periplasm (Gay et al, 1985). Thus, positive selection for sucrose resistance allows the collection of mutants with an allelic exchange.…”
Section: Strains and Plasmidsmentioning
confidence: 99%
“…and analysing their plasmid profiles. Rhizobial cells cured of the labelled plasmid and thus rendered capable of growing on sucrose (Gay et al 1985) can be identified and recovered by growing on sucrose-containing medium and confirmed by their loss of resistance to Km and by plasmid profile analysis.…”
Section: Introductionmentioning
confidence: 97%
“…It seems likely that while the pUC oriV is functional in PstQ, its transcription signals [especially the RNAII promoter (Polaczek & Ciesla, 1984)] are not well recognised in Pseudomonas. This situation sets up an unusual type of IS trap based on activation of plasmid replication, rather than on activation of silent resistance genes (Schneider et al, 2000), or inactivation of toxic genes (Gay et al, 1985;Simon et al, 1991). The repliconactivation IS trap discovered here may be useful in other contexts for detection of MGE activity and discovery of MGEs in other bacteria.…”
Section: Discussionmentioning
confidence: 99%